Measurement of the pp̄→WZ+X cross section at s=1.96TeV and limits on WWZ trilinear gauge couplings - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (American Physical Society (APS), 2007)
We present measurements of the process pp̄→WZ+X→ℓ′ νℓ′ℓ̄ at s=1.96TeV, where ℓ and ℓ′ are electrons or muons. Using 1fb-1 of data from the D0 experiment, we observe 13 candidates with an expected background of 4.5±0.6 events and measure a cross section σ(WZ)=2.7-1.3+1.7pb. From the number of observed events and the Z boson transverse momentum distribution, we limit the trilinear WWZ gauge couplings to -0.17≤λZ≤0.21(ΔκZ=0) at the 95% C.L. for a form factor scale Λ=2TeV. Further, assuming that Δg1Z= ΔκZ, we find -0.12≤ΔκZ≤0.29(λZ=0) at the 95% C.L. These are the most restrictive limits on the WWZ couplings available to date. © 2007 The American Physical Society.